PENGARUH TRICHOKOMPOS ALANG-ALANG TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELADA (Lactuca sativa L.) - Erni Diana BR Silalahi; Husna Yetti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The study aims to determine the effect of reed trichocompost on the growth and yield of lettuce (Lactuca sativa L.). This research has been conducted on the Experimental Station of Faculty of Agriculture, Universitas Riau, Pekanbaru from July to September 2017.  This study was performed experimentally by using completely randomized design (CRD) consisting of six treatments and three replications. Each unit of the experiment was consisted of three  crop cress. The treatments of reed trichocompost were, 0: without trichocompost. , T1: 2 ton. ha-1 (200 g. m-2 reed trichocompost., T2 : 4 ton.ha-1 (400 g.m-2) reed trichocompost, T3 : 6 ton.ha-1 (600 g.m-2) reed trichocompost dose, T4  : 8 ton.ha-1 (800 g.m-2) reed trichocompost dose, T5 : 10 ton.ha-1 (1000 g.m-2) reed  trichocompost. Parameters those observed in this study were plant height (cm), leave number (blade), leaf area (cm2), fresh weight (g), and fresh weight feasible for consumption (g). Data were analyzed statistically, with by using ANOVA and Ducan’s at the level of 5%. The results showed reed trichocompost can improve plant growth, especially height, leave number, leaf area, fresh weight and fresh weight feasible for consumption. Keywords: Lactuca sativa L. and reed trichocompost.